A política externa do México no início do século XXI: constrangimentos na busca por autonomia - Franzoni, Marcela (2018)
The dissertation analyzes the limited scope of the cooperation mechanisms with Latin America in which Mexico invested in the first years of the 21st century, especially the Community of Latin American and Caribbean States and the Pacific Alliance. The dual relationship with the United States, of dependence and interdependence, limits Mexico's possibilities of foreign policy, especially of using potential ties with Latin America as a counterweight to the overwhelming presence of the great northern neighbor. The possibilities for Mexico to increase its autonomy in this way are restricted, since these initiatives are not very formalized and have limited capacity to boost their foreign trade. However, relations of interdependence with the United States allow the country to exploit the magnitude of established economic and social bonds and create spaces to advance certain policies. This dichotomy explains, for example, why Mexico failed to advance a migration policy with the US but did not agree to negotiate the petroleum issue in NAFTA in the early 1990s. The initiatives of the 2000s sought to respond to four cyclical and structural incentives : frustration in relations with the United States, China's economic rise, the effects of the 2008-2009 economic- financial crisis in Mexico and relations with Latin America. Although it was an attempt to expand their international partnerships, they did not imply a revision of Mexico's international insertion strategy, which continued to favor its relations with the United States. In times of instability in bilateral relations, the Mexican government insists on the need to diversify the country's international economic relations, which has become a rhetorical goal. We conclude that Mexican foreign policy seeks to increase its autonomy by strengthening relations of interdependence, since any other possibility would imply a revision in its strategy of international insertion and in its model of economic development